1. The problem statement, all variables and given/known data Whenever base b is even (b=2k for some integer k) a number H=(d(n-1)d(n-2)...d1d0)b is even <=> d0 is even. 2. Relevant equations 3. The attempt at a solution I have formulated a proof for the forward direction (=>) but I am having trouble getting started on a proof for the backwards direction (<=) starting with the fact that d0 is even. Any advice would be much appreciated. I know all the definitions I'm just unsure how to build from d0 is even.